Methyl jasmonate-induced defense responses are associated with elevation of 1-aminocyclopropane-1-carboxylate oxidase in Lycopersicon esculentum fruit - Yu, Mengmeng (Journal of plant physiology, 2011)
Copyright © 2011 Elsevier GmbH. All rights reserved.